1866 Utah Acts 51, ch. 22, tit. 2, § 14 - (:unkn) unknown (My University, 1865)
If such offender, at the time of such robbery, is armed with a dangerous weapon, with intent, if resisted, to kill or maim the person robbed; or if, being so armed, he wound or strike the person robbed; or if lie have :any confederates aiding and abetting him in such robbery present, and so armed; he shall be punished by imprisonment for a term of not exceeding twenty-five years, and not less than ten years."
Keywords: COMMITTING CRIME W/ WEAPON